Uma visão colonial do racismo - Rui M. Pereira (Cadernos de Estudos Africanos)
In 1959 António Jorge Dias, anthropologist, was invited to lecture Portuguese Culture in the university of Witwatersrand, in Johannesburg. Since 1957 he had been carrying out research work in the north of Mozambique, in the Makonde Plateau, reporting his observations on the political and social situation of the colony to the Portuguese government, in Lisbon. That period of time in South Africa provided him with further information of analysis which allowed him to develop a «comparative framework» between the political ruling model of the Portuguese colonialism — the so called «assimilation» — the indirect rule of the British colonialism he could observe in Tanganyika and the apartheid system in South Africa. This text does not analyse the current reconfiguration of that memory. However, it helps perceive that in the late 50s Jorge Dias's points of view were already leading towards the assertion of the paradigm of lusotropicalism which even today shapes the minds of large sectors of Portuguese society.